A mouse model of deep vein thrombosis by inferior vena cava hypoperfusion using ameroid constrictors - Hiroko Tadokoro; Yukihide Ota; Mari Uomoto; Shiro Koizume; Shinya Sato; Yoshiyasu Nakamura; Mitsuyo Yoshihara; Yoko Endo-Takahashi; Yoichi Negishi; Etsuko Miyagi; Yohei Miyagi (Scientific Reports)
Abstract Traditional mouse models for deep vein thrombosis (DVT), frequently utilized in research focused on cancer-associated thrombosis (CAT), reliably induce thrombus formation by obstructing blood flow (BF) in the inferior vena cava (IVC), which does not occur in humans. Therefore, to develop a new DVT model for CAT studies, we implanted an ameroid constrictor (AC), a hygroscopic casein C-shape device, around the IVC and aorta of immunocompromised mice. We evaluated the thrombus 3 and 8 days post-AC implantation and compared it with the traditional model 2 days post-vena cava ligation. The size of each thrombus was measured, and the composition was assessed using histological staining; BF through the IVC was confirmed using ultrasound imaging. The thrombus size variability in the AC and ligation models was equivalent. Compared with thrombi on day 3 post-AC implantation, those on day 8 showed characteristics of human thrombi in the subacute to chronic stage. The BF in the IVC was maintained even on day 8. In summary, the AC model showed reproducibility with no significant difference in thrombus size variability from the traditional ligation model while maintaining the BF of the IVC.